Push or Pull: Recommendations and Alternative Approaches for Public Science Communicators - Schmitt, Catherine V. (Frontiers in Communication, 2018)
The news media is a primary way that science is communicated to American adults. News stories are driven by press releases and other communications “pushed” by institutions, publishers, organizations, and private companies. This article, from the perspective of a public science communicator, examines and critiques push communications, offers some best practices for press releases, and presents examples of other “pull” approaches to communicating science that more closely align with both the process of science and with the interests and values of public audiences.